Case Report: Durable response to immuno-chemotherapy in a case of ROS1 fusion-positive advanced lung adenocarcinoma: A case report - Yan, Ningning; Huang, Siyuan; Li, Linlin; Guo, Qianqian; Geng, Di; Zhang, Huixian; Guo, Sanxing; Li, Xingya (Frontiers in Pharmacology, 2022)
Immune checkpoint inhibitors (ICIs) have greatly transformed the treatment and improved the prognosis for patients with non-small cell lung cancer (NSCLC) without driver gene alterations. However, the effects of ICI combination therapy in ROS1 fusion-positive NSCLC remains unclear. Herein, we present a case with ROS1 fusion-positive NSCLC treated with ICI plus chemotherapy. The patient achieved a continuous partial response (PR) to ICI plus chemotherapy and a more than 35 months progression free survival. This case demonstrates that ICI plus chemotherapy is a promising option for patients with ROS1 fusion-positive NSCLC.